Exclusive breastfeeding practices and factors affecting them in urban areas of Uttar Pradesh - Prakhar Sharma; Neha Bansal; Abha Kaul (Journal of Family Medicine and Primary Care)
Background: Exclusive breastfeeding for the first 6 months is the recommended infant feeding practice, with established benefits. In India, exclusive breastfeeding rates have seen some improvement, but Uttar Pradesh has experienced a decline. Various factors influence breastfeeding practices, such as socio-cultural beliefs, maternal knowledge, and support. Considering urbanization, industrialization, and a significant migrant population, it is crucial to understand the determinants of breastfeeding practices in urban Uttar Pradesh. This study aimed to fill these knowledge gaps by examining factors influencing breastfeeding practices in the region. Methods: This cross-sectional study was conducted at Sharda Hospital’s Pediatrics Outpatient Department (OPD) in Uttar Pradesh over 1.5 years from January 1, 2019 to June 30, 2020. The minimum sample size of 96 was determined for the study. Study participants included 200 mothers with children aged 6 months to 2 years attending the Pediatrics OPD. Data were collected through a 42-item questionnaire administered by trained interviewers who ensured privacy and comfort. Data analysis was performed using Statistical Package for Social Sciences, including descriptive statistics and the Chi-square test for categorical variables (P < 0.05). Results: The study involved 200 mothers with children aged 6 months to 2 years attending a Pediatrics OPD in Uttar Pradesh. Mothers aged 21–30 years (78%) were predominant. Among the children, 62.5% were male. Colostrum was given by 86% of mothers, and 40% introduced pre-lacteal feeds. Exclusive breastfeeding was practiced by 60% of mothers. The analysis did not show statistically significant differences based on socio-economic status, maternal education, or occupation (P > 0.05). Conclusion: In conclusion, the findings from this study provide a comprehensive understanding of feeding practices among mothers in urban areas of Uttar Pradesh. While many mothers adhere to recommended practices, there is room for improvement in reducing pre-lacteal feeding and promoting exclusive breastfeeding.